2019
DOI: 10.1039/c9nj01697j
|View full text |Cite
|
Sign up to set email alerts
|

Porous composite CMC–KCuFC–PEG spheres for efficient cesium removal from wastewater

Abstract: Highly stable porous composite CMC–KCuFC–PEG was used for Cs+ recovery from wastewater, and showed excellent adsorption performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…2(b)). 24 The SEM and TEM images shown in Fig. 2 revealed that Prussian blue analogs were generated both on the surface and inside of the PBA@CuAl-LDH.…”
Section: Pccp Papermentioning
confidence: 94%
“…2(b)). 24 The SEM and TEM images shown in Fig. 2 revealed that Prussian blue analogs were generated both on the surface and inside of the PBA@CuAl-LDH.…”
Section: Pccp Papermentioning
confidence: 94%
“…21,22 CMC can form insoluble gel spheres in the presence of multivalent metal ions such as Fe 3+ , Cu 2+ and Al 3+ . [23][24][25] Recently, Zong et al synthesized CMC-KCuFC composite microspheres with Cu 2+ as a crosslinking agent, and the particles were able to maintain high stability aer separation. 26 However, the secondary pollution caused by the release of trace Prussian blue would lead to serious threat to the water body.…”
Section: Introductionmentioning
confidence: 99%